ANALISIS HASIL CETAKAN MATERIAL POLYPROPYLEN BENTUK BOTOL MENGGUNAKAN METODE INJECTION BLOW MOLDING: Analysis of Bottle Shaped Polypropylene Material Mold Results using The Injection Blow Molding Method - Sugiyanto, Didik; Wicaksono, Enggar Darmawan; Daryus, Asyari (Jurnal Konversi Energi dan Manufaktur, 2024)
The process of forming materials is often carried out in the manufacturing industry, especially in the process of forming plastic materials. One method is the injection blow molding, which is done by blowing air into a mold that has been previously designed. The need for a level of precision and accuracy in designing a mold using the injection molding process is one of the important things in the injection blow molding process. One of the designs that must be considered when printing a bottle-shaped product is that it must be precise, in accordance with the expected product design, by considering machine and mold design, material selection, molding materials, and manufacturing processes. The aim of the research is to determine the influence of temperature and pressure on thickness and shrinkage in molds with 30 ml bottle shape. From the results of tests that have been carried out, the effect of a pressure of 4 bar and a temperature of 160 °C produces an average thickness of the mold of 1.03 mm, while at a pressure of 4 bar and temperature of 180 °C the average thickness is 1 mm. The standard used for bottle products is less than 1 mm so that the pressure 4 bar from the experimental results meets the standards for injection blow molding process mold results and for shrinkage occurs at 0.681 %.